Application Progress of Transcranial Direct Current Stimulation Combined with Limb Therapy in Rehabilitation of Lower Limbs after Stroke - CHEN Hanbo; LU Xiao; ZHENG Wenhua; GUO Yongliang; YAN Tiebin (康复学报)
Motor dysfunction of lower extremities is one of the most common and urgent problems to be solved in patients with stroke. Even if early and standardized rehabilitation therapy, there are still many patients who cannot restore their walking function or have serious abnormal gait after 6 months of onset. It has a great impact on their daily activities and self-care ability, and brings a heavy economic burden to the society and family financial situation. Rehabilitation interventions for motor dysfunction of lower extremities include central intervention techniques and peripheral intervention techniques. Central intervention technology stimulates the brain, such as neuroregulation and scalp acupuncture, while peripheral intervention technology stimulates limbs, such as functional electrical stimulation (FES) and robot-assisted gait training (RAGT). Although the two technologies have different stimulation targets, the same purpose, previous studies found that the treatment effect was better when combined application of effective central intervention technology with peripheral intervention technology. It is called "brain-limb coordinated regulation therapy technology", which can be divided into brain-upper-limb coordinated therapy mode and brain-lower-limb coordinated therapy mode according to different coordinated parts. The technology can be divided into synchronous brain-limb coordination therapy mode and asynchronous brain-limb coordination therapy mode according to the different coordination sequence. The asynchronous mode can be further divided into the mode of stimulating the brain first and then the limbs, and the mode of stimulating the limbs first and then the brain. At present, this technique is widely used in clinical research. Transcranial direct current stimulation (tDCS) is widely used in combination with lower limb rehabilitation therapy because of its advantages such as high safety, easy to carry equipment and long delayed effect time. However, the therapeutic effect of this kind of synergistic therapy is quite different, due to the different lower limb rehabilitation techniques and different sequence involved in the synergistic therapy. This article reviews the application progress of tDCS with different treatment parameters combined with different lower limb rehabilitation techniques and different cooperative treatment sequence in stroke, and discusses the factors which affect the effect of cooperative treatment and the possible effective cooperative treatment mode, in order to provide new ideas for the treatment of lower limb dysfunction after stroke.